Model Hybrid Learning Indoor And Outdoor Untuk Meningkatkan Layanan Interaksi Sosial Penyandang Disabilitas Usia Dini - Sartinah, Endang Pudjiastuti; Andajani, Sri Joeda; Pamuji, Pamuji; Nurismawan, Ach. Sudrajad (Universitas Nusantara PGRI Kediri, 2022)
This development research specifically aims to test the feasibility of indoor and outdoor hybrid learning model products in improving social interaction services for people with disabilities at an early age for kindergarten educators. This development research uses the Educational Research Development model design from Gall, Gall & Borg (2003). The application of the product feasibility test is carried out through expert and practical tests. Collecting data obtained from expert testing and practicality were analyzed using the percentage technique. Furthermore, the results of the accuracy of the indoor and outdoor hybrid learning model are packaged in a web network so that it can be used at any time and is flexible through learning innovations from each region, specifically to provide social interaction services for people with early age disabilities. Based on the feasibility level test of the model from the assessment of 2 PAUD and PLB experts, it was stated that the indoor and outdoor hybrid learning model product to improve social interaction services for people with early age disabilities for inclusive kindergarten educators could be used for testing, after being revised.